Strength in the Face of Adversity: Resilience Among Mexican Nationals and Mexican Immigrants to the United States - Morgan Consoli, Melissa L.; Gonzales, Rufus R. (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
This exploratory, qualitative study looks at resilience in Mexican Nationals and Mexican Immigrants. Eight Mexican Nationals and six Mexican Immigrants participated in one to three hour semi-structured interviews that asked about their perceptions of stressors, motivation and success in life. Participant responses were analyzed thematically for resilience using Thematic Analysis (Boyatzis, 1998). Contrastive Analysis of themes indicated that resilience can differ based on cultural circumstances (i.e., Mexican National/Mexican Immigrant) given that barriers and therefore potential gains differ by population. In further results, resilience was highlighted as the result of a process, or combination and interaction of experiences as opposed to being due to any specific trait. Specific emergent themes for facilitating resilience included Environmental Resources, Positive Attitudes, and Response Frameworks. Limitations, suggestions for future research, and implications for psychologists are discussed.